Earthquake-Induced Landslides Proceedings of the International Symposium on Earthquake-Induced Landslides, Kiryu, Japan, 2012 - Ugai, Keizo; Yagi, Hiroshi; Wakai, Akihiko; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Seismicity is a major trigger for landslides with often devastating effects. The Japan Landslide Society (JLS) therefore organized a meeting fully dedicated to the research area of earthquake induced landslides. The symposium covers all aspects of earthquake-induced landslides including the phenomena occurred in manmade embankments as well as in natural slopes in mountainous areas. In this comprehensive volume on landslide science the JLS presents the Proceedings of this First International Symposium on Earthquake-Induced Landslides, held in November 2012 in Kiryu, Japan.
Investigation of recent and historical earthquake-triggered landslides and their impacts -- Characteristics, processes and mechanisms of earthquake-triggered landslides -- Physical and numerical modeling of earthquake-triggered landslides.-Instrumentation and monitoring technologies for earthquake-related landslides -- Risk assessment and management of earthquake-related landslides -- Stabilization and disaster mitigation of earthquake-related landslides -- Earthquake-related landslide dams and their risk assessment and management.-Monitoring, prediction and early warning systems for post-earthquake landslides and debris flows -- Other relevant topics concerning earthquake-related landslides.
Keywords: Geography; Geology; Ecology; Earth Sciences; Natural Hazards; Geotechnical Engineering & Applied Earth Sciences; Geoecology/Natural Processes